Optimising Macroeconomic Learning through Integration of Contextual Case Studies and Mathematical Modelling - Ruslan, Dede; Siregar, Kiki Hardiansyah (Jurnal Pengabdian West Science, 2025)
Macroeconomics learning often faces challenges in conveying complex abstract concepts to students. This paper aims to optimise macroeconomic learning by integrating contextual case study approach and simple mathematical modelling. This educational service method involves training and mentoring students in analysing real cases of economic policy using mathematical models to improve their understanding and literacy of economic policy. The evaluation results showed a significant improvement in analytical skills and understanding of macroeconomic concepts, especially related to the impact of endid and monetary policies. This approach is recommended as an innovative learning model to improve the quality of macroeconomic education.